2022
DOI: 10.21203/rs.3.rs-2381024/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated gut metabolome and microbiome fingerprinting reveals that dysbiosis precedes allergic inflammation in IgE-mediated pediatric cow’s milk allergy

Abstract: Understanding the underlying mechanisms behind IgE-mediated cow’s milk allergy (IgE-CMA) is imperative for the discovery of novel biomarkers and the design of innovative treatment and prevention strategies. Here, we report data on the gut microbiome, metabolome, and lipidome of 81 children affected by food allergies, including CMA and healthy controls. Moreover, we developed a mouse model that mimicked IgE CMA best, BALB/c mice sensitized with ß-lactoglobulin using cholera toxin. During sensitization, we obser… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Therefore, it is necessary to compare metabolites using samples collected from study groups, considering factors such as age, types or number of FA, dietary restrictions, and diagnostic methods. Recently, a study addressing these limitations by considering them in the study design has been reported 90 . The study focused on children with milk allergy who were placed on dietary restrictions, comparing the metabolites in the subacute or chronic state, while metabolic analysis related to acute allergic reactions associated with sensitization and allergic inflammation was conducted through the animal model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to compare metabolites using samples collected from study groups, considering factors such as age, types or number of FA, dietary restrictions, and diagnostic methods. Recently, a study addressing these limitations by considering them in the study design has been reported 90 . The study focused on children with milk allergy who were placed on dietary restrictions, comparing the metabolites in the subacute or chronic state, while metabolic analysis related to acute allergic reactions associated with sensitization and allergic inflammation was conducted through the animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study addressing these limitations by considering them in the study design has been reported. 90 The study focused on children with milk allergy who were placed on dietary restrictions, comparing the metabolites in the subacute or chronic state, while metabolic analysis related to acute allergic reactions associated with sensitization and allergic inflammation was conducted through the animal model. Finally, although various distinct metabolites have been identified in FA, their specific roles in FA are still relatively poorly understood.…”
Section: Con Clus Ionmentioning
confidence: 99%